Surface Roughness of Restorative Materials After Simulated Toothbrushing with Toothpastes Containing Theobromine and Arginine: An In Vitro Study - Öcal, Fikri; Dayi, Burak; Küçükakçalı, Zeynep (UI Scholars Hub, 2023)
Objective: This study examined the effect of toothpastes containing theobromine and arginine on the roughness changes of microhybrid composite, nanohybrid composite, and giomer restorative materials. Methods: A total of 90 disc-shaped specimens were prepared using microhybrid composite (Arabesk-Ara), nanohybrid composite (Herculite-Her), and giomer (Beautifil II-Gio). The samples were divided into 3 subgroups (n = 10), and initial surface roughness was evaluated with a mechanical profilometer and scanning electron microscopy (SEM). All samples were then subjected to a 1-year brushing simulation via a toothbrushing simulator using toothpastes containing theobromine (Theodent Classic, Theodent) or arginine (Colgate PRO-Relief, Colgate Palmolive); a control group was brushed with distilled water. Afterward, surface roughness measurements and SEM images were re-recorded. The difference in surface roughness was statistically evaluated. Results: The toothpaste containing arginine caused the highest increase in surface roughness in all groups. The toothpaste containing theobromine showed the least increase in roughness in the Her and Gio groups. Conclusion: Using toothpaste containing theobromine causes the least increase in the surface roughness of restorative materials, while using toothpaste containing arginine causes the greatest increase.